The Moderating Role of Sociodemographic Factors in the Relationship Between Physical Activity and Subjective Well-Being in Chilean Children and Adolescents - Cespedes-Carreno, C (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Background: The relationship between physical activity habits and well-being is widely recognized; however, the interaction that these variables have with sociodemographic factors throughout life is only partially addressed in the literature, particularly in children and adolescents. The aim of this article is to analyze the moderating effect of sociodemographic factors and the possible interaction of these moderations in the relationship between physical activity and subjective well-being in children and adolescents. Methods: This cross-sectional study considered a sample of 9572 children and adolescents from 10 to 19 years of age, students of primary and secondary schools in all regions of Chile. Subjective well-being and physical activity habits were measured using selfreport questionnaires. Socioeconomic level was established from the school vulnerability index (SVI) of each student’s school. Results: Simple moderation analyses revealed that the higher the age and the lower the SVI, the stronger the relationship between physical activity habits and subjective well-being. From a double moderation analysis, it could be observed that the age of the subjects is the most relevant moderator in the relationship between physical activity habits and perceived wellbeing in young people. Conclusions: This study highlights the importance of considering these factors and their interaction when generating programs or public policies to improve physical activity habits and well-being in children and adolescents. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.